More than Teach: English Teachers’ Advocacy in the Online Globalized Era - Artanti Puspita Sari (LINGUA: Jurnal Bahasa dan Sastra, 2018)
Abstract: This paper reviews how language educators and researchers have responded to issues in the online era, such as globalization, transnational migration, and global challenges. Online technology has triggered increasing globalization of businesses and has become a powerful means of communication for individuals in establishing and developing relationships across national boundaries. Furthermore, it has served to raise awareness of social, economic, and environmental challenges of the 21st century. In spite of its positive effects, online technology development results in a more demanding world which requires individuals to enhance their competitive ability. Improving the quality of education is paramount in strengthening the quality of human resources. Based on the review of language educators’ and researchers’ responses toward issues in the online era, the writer considers what English educators, particularly those in Indonesia, can do to advocate the enhancement of education quality through their roles as teachers, researchers, and community members. Keywords: globalization, language educators, online technology Abstrak: Makalah ini mengulas bagaimana para pendidik dan peneliti bahasa telah menanggapi isu-isu di era online, seperti globalisasi, migrasi transnasional, dan tantangan global. Teknologi dalam jaringan (online) telah memicu meningkatnya globalisasi bisnis dan telah menjadi sarana komunikasi yang penting bagi masyarakat dunia dalam membangun dan mengembangkan hubungan lintas batas negara. Selain itu, teknologi online telah meningkatkan kesadaran akan tantangan sosial, ekonomi, dan lingkungan abad ke-21. Terlepas dari efek positifnya, pengembangan teknologi online menuntut sumber daya manusia untuk meningkatkan kemampuan kompetitif mereka. Peningkatan kualitas pendidikan sangat penting dalam memperkuat kualitas sumber daya manusia. Berdasarkan tinjauan terhadap reaksi para pendidik bahasa dan peneliti terhadap isu-isu di era online, penulis memberikan rekomendasi mengenai apa yang dapat dilakukan oleh para pendidik bahasa Inggris, khususnya yang ada di Indonesia, untuk mengadvokasi peningkatan kualitas pendidikan melalui peran mereka sebagai guru, peneliti, dan anggota masyarakat.Kata-kata kunci: globalisasi, tenaga pendidikan Bahasa Inggris, teknologi dalam jaringan